Neo-Philanthropy - Kaspar Villadsen (Social Work and Society)
Neo-philanthropy refers to the re-emergence of philanthropic activities and a growing public trust in those who carry them out as ameliorators of societal and social issues. The original term 'philanthropy' designates the donating of money or services for societal purposes or for the benefit of specific groups with some perceived need. Further, it is understood that philanthropic activities are guided by some kind of moral, religious, or humanitarian principles. The term has a rather broad range of applications, since it may both designate funding bodies that offer charitable donations and non-governmental organisations and specific services run by volunteers to help different target groups. Charitable trusts may offer philanthropic aid for diverse purposes which allegedly supersede the state's capacity for action, such as the promotion of business ethics, the strengthening of community participation, health improvement, poverty-reduction, improvement of education levels, or democratic participation. In the 19th century heydays of philanthropic poor relief, the helpers and organizers of work for the poor were called 'philanthropists'. Nowadays, this term is largely reserved for persons engaged in charitable trusts which donate private resources for social and educational purposes.